A Precocious Cerebellar Ataxia and Frequent Fever Episodes in a 16-Month-Old Infant Revealing Ataxia-Telangiectasia Syndrome - Luigi Nespoli; Annapia Verri; Silvia Tajè; Francesco Paolo Pellegrini; Maddalena Marinoni (Case Reports in Immunology)
Ataxia-telangiectasia (AT) is the most frequent progressive cerebellar ataxia in infancy and childhood. Immunodeficiency which includes both cellular and humoral arms has variable severity. Since the clinical presentation is extremely variable, a high clinical suspicion will allow an early diagnosis. Serum alpha-fetoprotein is elevated in 80–85% of patients and therefore could be used as a screening tool. Here, we present a case of a 5-year-old female infant who was admitted to our department at the age of 16 months because of gait disorders and febrile episodes that had begun at 5 months after the cessation of breastfeeding. Serum alfa-fetoprotein level was elevated. Other investigations showed leukocytopenia with lymphopenia, reduced IgG2 and IgA levels, and low titers of specific postimmunization antibodies against tetanus toxoid and Haemophilus B polysaccharide. Peripheral lymphocytes subsets showed reduction of T cells with a marked predominance of T cells with a memory phenotype and a corresponding reduction of naïve T cells; NK cells were very increased (41%) with normal activity. The characterization of the ATM gene mutations revealed 2 specific mutations (c.5692C > T/c.7630-2A > C) compatible with AT diagnosis. It was concluded that AT syndrome should be considered in children with precocious signs of cerebellar ataxia and recurrent fever episodes.